Determinants of awareness on ownership decision for Takaful medical policy among youth in Malaysia - Mohd Amin, Ismail (2018)
The main purpose of this study is to determine the factors that affect the awareness and ownership decision to subscribe Takaful medical policy among youth in Malaysia. In addition, this study attempts to profile the policyholders and compare this against the profile of non-policyholders within demographics factors (gender, marital status, income, disposal savings, profession, education level, profession sectors, age group, as well as critical illness). A model for ownership and non ownership decision is also proposed in this study. Specifically, two objectives established to compare the different between ownership and non-ownership in tendency to subscribe Takaful medical policy. Besides that, this study also tried to clarify the relationship between three factors of awareness and ownership decision to subscribe Takaful medical policy which is source of general information, general information features, as well as religion. The study was conducted among 324 youth whom aged between 18 years old to 35 years old, residing in Kedah. The finding of this study suggests that there are significant relationship between general information features and religion towards the determinants of Takaful medical policy among youth in Kedah. Meanwhile, findings for source of general information show that there is a significant relationship towards non-ownership decision to subscribe Takaful medical policy. As a conclusion, finding of this study clearly demonstrated that factor of ownership and non-ownership decision of Takaful medical policy among youth in Malaysia.